O papel do óxido nítrico no núcleo paraventricular do hipotálamo em condições de exercício e hipóxia - Bruna Lima Costa Zuquim Nunan (2020)
The paraventricular nucleus of the hypothalamus (PVN) in an important site for autonomic and neuroendocrine control. In addition, this nucleus projects to preoptic area (POA), the main integrative thermoregulation center, and its pre-autonomic neurons also project directly to the intermedium lateral column, the main site of sympathetic outflow that controls thermoeffector organs. In addition, PVN neurons express the neuronal isoform of nitric oxide synthase (nNOS), the main enzyme in the conversion of L-Arginine in nitric oxide (NO), a gaseous transmitter in Central Nervous System. It is known that physical exercise increases nNOS expression in PVN. In addition, PVN has direct connections to brainstem nuclei that controls ventilation, and it is known that PVN participates in peripheral chemoreflex and neurons that express nNOS are active in acute hypoxia exposure. Therefore, the present study had three main objectives: i) to evaluate the role of NO in PVN in the thermoregulation in acute progressive exercise; ii) evaluate the role of NO in PVN in the ventilatory responses to acute hypoxia; and iii) evaluate the effect of nNOS inhibition in PVN in the anapyretic response to exposure to hypoxia. The study was divided in two experimental protocols. For the experimental protocol 1, male Wistar rats were used. Bilateral microinjections of the drug Nw-Propyl-L-Arginine (NPLA) were performed in PVN at doses of 0.4 nmol/100nL (N=10) or 0.04nmol/100 nL (n=10) or vehicle (NaCl 0,15M) (n=12), and animals were submitted to an acute progressive exercise running on a treadmill. Thermal and performance variables were collected. For experimental protocol 2, 16 male Wistar rats were used. Pulmonary ventilation (V ̇E) and abdominal temperature (Tabd) were measured at baseline, before NPLA microinjection into the PVN and before the beginning of hypoxia. After the microinjection, animal remained one hour in hypoxia exposure (7% O2). Ventilation data were collected every 20 minutes. At progressive exercise protocol, the animals that receive the highest dose of the drug (0.4 nmol/100nL) presented an attenuation in fatigue Tabd when compared to vehicle group (38.28 ± 0.22 °C vs. 39.35 ± 0.16 °C, p = 0.005). There was no difference in Ttail and Hthr between groups. In contrast, Hsen was increased in NPLA 0.4 group, compared to vehicle, indicating that in these animals, Tabd was attenuated during exercise (NPLA 0.4: 13.74 ± 1.45 vs. vehicle: 8.84 ± 0.91, p < 0.05). Heat storage was lower in NPLA 0.4 compared to vehicle group vehicle (335.14 ± 39.44 cal vs. 569.61 ± 51.63 cal, p = 0.014). The inhibition of nNOS in PVN worsened the performance of animals that received the lowest dose (0.04 nmol/100nL). In experimental protocol 2, there was no difference in the hypoxic ventilatory and thermal responses between NPLA (n=8) and vehicle (n=8) groups. These results suggest that NO in PVN is necessary for the proper thermal regulatory mechanisms in progressive exercise, facilitating regulatory mechanisms of hyperthermia. In contrast, at the dose used in experimental protocol 2, the results suggest that endogenous NO do not play a significant role in the thermal and ventilatory responses to acute hypoxia.